Performance Of Carbide Tool In High Speed Turning Of TI-6AL-4V ELI Under Conventional Coolant And Minimal Quantity Lubrication - Che Haron, Che Hassan; Sulaiman, Mohd Amri; A Ghani, Jaharah; Kasim, Mohd Shahir; Mohamad, Effendi (Asian Research Publishing Network (ARPN), 2016)
The purpose of the study is to evaluate the tool life performance of uncoated carbide and the quality of machined surface, focusing on roughness surface values in high speed turning of titanium alloy, Ti-6Al-4V extra low interstitial (ELI), under minimal quantity lubrication (MQL) and conventional coolant. The cutting parameters were arranged using the Box-Behnken design of experiment. Meanwhile the cutting parameters; cutting speed, vc (120, 170, and 220 m/min), feed rate, f (0.1, 0.15, and 0.2 mm/rev), and depth of cut, ap (0.4, 0.5, and 0.6 mm) were applied. The effects of two types of coolant were observed and the results shown that the cutting tool turned under MQL has a longer tool life (25%) and leads to reduce surface roughness of machined surface (30%) compared with that turned under the conventional coolant condition. It was proven that the MQL condition is a good alternative in replacing the conventional coolant.